The impact of natural resource endowment and transportation infrastructure on China's regional green economic performance in the context of COP26. (December 2022) - Xu, Guoyin; Jiang, Jinde; Wang, Rong
Abstract: In the context of the 26th UN Climate Change Conference of the Parties (COP26), this paper proposes at COP26 that to address climate change and promote world economic recovery, it is necessary to maintain a multilateral consensus, focus on pragmatic actions and accelerate green transformation. Therefore, the improvement in green economic performance has become the focus of academic attention, but existing research mainly measures its value, there are few studies carried out in the context of COP26, and this study is a supplement and extension to the existing research field. This paper explores the impact of transportation infrastructure and natural resource endowment on the green economic performance (GEP). The study selects the slacks-based measure (SBM) model to measure China's regional green economic performance from 2007 to 2020, analyze the temporal and spatial differences in the GEP in each region, and then uses the system Gaussian mixture model (GMM) to verify the relationship among the three. The conclusions are as follows: (1) The annual overall average of the national green economic performance was 0.538, the overall level was not high, and there were significant differences between regions, showing a gradually decreasing trend from east to west. (2) Natural resource endowment had a negative impact on the GEP of the whole country and the central and western regions; the eastern region showed significant positive characteristics on the "U"-shaped features of the transportation infrastructure on the GEP across the country and the west. The impact on the green economic performance in the eastern region had an obvious inhibitory effect and negative impact on the GEP in the central region. (3) The first-order coefficients of the intensity of the environmental regulations at the national level and in the three regions were significantly negative and showed U-shaped characteristics; foreign direct investment can improve GEP at the national level and have the same effect in eastern and western China but will not be significant in the central region. Industrial structure's impacts on GEP at the national level and in the three regions were all negative, which hindered the improvement of green economic performance. Urbanization had an obvious inhibitory effect on GEP at the national level and in central and western China, but urbanization promote eastern GEP. The research in this paper has important significance as a reference for improving the performance of China's regional green economic performance and achieving the Sustainable Development and COP26 goals. Highlights: An input-output index system was constructed. Measure GEP using the SBM model. Use the system GMM to verify the influencing factors of GEP. Make recommendations to improve green economy performance.